2019
DOI: 10.3390/microorganisms7110525
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Microbial Community of Phyllosphere Associated with Five Tropical Plants on Yongxing Island, South China Sea

Abstract: The surfaces of a leaf are unique and wide habitats for a microbial community. These microorganisms play a key role in plant growth and adaptation to adverse conditions, such as producing growth factors to promote plant growth and inhibiting pathogens to protect host plants. The composition of microbial communities very greatly amongst different plant species, yet there is little data on the composition of the microbiome of the host plants on the coral island in the South China Sea. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In this study, we found that plant compartment exerted a signi cant effect on bacterial diversity, with the highest and lowest values observed in rhizospheric soil and leaf-endophytic habitats, respectively. Previous studies demonstrated that higher bacterial diversities were observed in soil compared with root endophytic and phyllospheric compartments of various plants (e.g., [10,31]), mostly due to the more complex heterogeneity and broad niches of soil circumstance. However, we surprisingly found that the leaf-epiphytic bacteria showed equally high OTU richness as the root, indicating that the relatively high bacterial diversity inhabiting on the leaf surface of subtropical tree species.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that plant compartment exerted a signi cant effect on bacterial diversity, with the highest and lowest values observed in rhizospheric soil and leaf-endophytic habitats, respectively. Previous studies demonstrated that higher bacterial diversities were observed in soil compared with root endophytic and phyllospheric compartments of various plants (e.g., [10,31]), mostly due to the more complex heterogeneity and broad niches of soil circumstance. However, we surprisingly found that the leaf-epiphytic bacteria showed equally high OTU richness as the root, indicating that the relatively high bacterial diversity inhabiting on the leaf surface of subtropical tree species.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that plant compartment exerted a signi cant effect on bacterial diversity, with the highest and lowest values observed in rhizospheric soil and leaf habitats, respectively. Previous studies demonstrated that higher bacterial diversities were observed in soil compared with root endophytic and phyllospheric compartments of various plants (e.g., Bao et al 2019;Sun et al 2021), mostly due to the more complex heterogeneity and broad niches of soil circumstance. However, we surprisingly found that the leaf-associated bacteria showed equally high OTU richness as the root, indicating that the relatively high bacterial diversity inhabiting on the leaf surface of subtropical tree species.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the use of the two ITS regions has been quite inconsistent. While some used ITS2 as the universal fungal barcode (Bao et al 2019;Beng Fig. 4 Heatmap of the most common taxa based on their consistency in North-eastern Brazil Caatinga leaves (BC) and sap-feeding insects (BC*), Northeastern Brazil Tropical Rainforest (BR), Europe alpine zone (EA), and Central Europe colline zone (EC) samples.…”
Section: Applied Methodsmentioning
confidence: 99%
“…The use of operational taxonomic units (OTUs) versus the recent use of amplicon sequence variants (ASVs) is also inconsistent. Although there are recommendations to use only ASVs (Callahan et al 2017), resulting in a reduction in the number of dominant species (Egidi et al 2019), many of the current studies are still based on OTUs (Bao et al 2019;Beng and Corlett 2019;Beule et al 2019;Checinska Sielaff et al 2019;Epstein et al 2019;Janakiev et al 2019;Lynikiene et al 2020;Morales-Rodriguez et al 2019;Nerva et al 2019;Pan et al 2019;Qian et al 2020;Ricks and Koide 2019;Saravesi et al 2019;Wilkinson et al 2019;Würth et al 2019;Yao et al 2019;Zhang et al 2019), but others rely on ASVs (Del Frari et al 2019;Egidi et al 2019;Li et al 2019), or OTUs generated from ASVs (Ezeokoli et al 2020), and even OTUs from cultivationbased Sanger sequencing are still in use (Janowsky et al 2019). With the availability of the VSEARCH tool within the QIIME2 pipeline, allowing the easy aggregation of OTUs from ASVs, the Illumina sequencing datasets in this Fig.…”
Section: Applied Methodsmentioning
confidence: 99%